New species of Colletotrichum from wild Poaceae and Cyperaceae plants in Iran. (2nd January 2022) - Alizadeh, A.; Javan-Nikkhah, M.; Nourmohammadi Nazarian, R.; Liu, F.; Zare, R.; Fotouhifar, K. B.; Stukenbrock, E. H.; Damm, U.
ABSTRACT: Twenty-two Colletotrichum strains were isolated from anthracnose symptoms or leaf spots on leaves of various wild Poaceae and Cyperaceae plants collected in three provinces of Iran and tentatively identified as belonging to the Graminicola species complex based on morphology. All strains were studied via a polyphasic approach combining colony characteristics, morphology and phylogeny inferred from multi-locus sequences, including the nuc rDNA ITS1-5.8S-ITS2 (ITS), partial sequences of the β-tubulin ( tub2 ), actin ( act ), manganese superoxide dismutase 2 ( sod2 ), DNA lyase 2 ( apn2 ) genes, a 200-bp intron of the glyceraldehyde-3-phosphate dehydrogenase ( gapdh ), and the intergenic spacer between the apn2 gene and the mat1 idiomorph ( apn2/mat1 ). Six species were distinguished, including three new species, namely C. caspicum, C. persicum, and C. sacchari, and three previously described species, C. cereale, C. nicholsonii and C. sublineola . Comprehensive morphological descriptions and illustrations are provided for all species. Furthermore, this study provided new insights into the distribution and host range of known species. GRAPHICAL ABSTRACT: uf0001